A review of the tolerability of the candidate TB vaccine, MVA85A compared with BCG and Yellow Fever vaccines, and correlation between MVA85A vaccine reactogenicity and cellular immunogenicity - Rowland, R; Brittain, N; Poulton, I; Minassian, A; Sander, C; Porter, D; Williams, N; Satti, I; Pathan, A; Lawrie, A; McShane, H (Elsevier, 2012)
Background: The development of a new, more effective vaccine against tuberculosis (TB) for use in healthy and HIV-infected adults, children and infants, remains a global health priority. MVA85A is a candidate tuberculosis vaccine designed to enhance immunity to the existing vaccine, Bacillus Calmette-Guerin (BCG). MVA85A entered clinical trials in 2002 and has now progressed to Phase IIb proof-of-concept efficacy trials in infants and HIV-infected adults in Africa. Methods: A detailed analysis was conducted of the cumulative safety data of intradermal delivery of MVA85A in 112 healthy adult subjects in a series of open label, single arm, non-controlled, Phase I safety and immunogenicity clinical trials in the UK. The trials differed with respect to previous mycobacterial exposure, vaccine regime and dose. Objective safety measures (local reaction size and body temperature) were evaluated for correlations with adaptive antigen-specific immune responses. Results: All subjects in the combined mid-dose group developed a local reaction, of which 92% were mild, 8% were moderate and no reactions were severe. Around 90% of subjects in each group reported at least one systemic adverse event, most commonly headache, myalgia, malaise, feeling feverish, fatigue and arthralgia. Of all systemic adverse events in the combined mid-dose group, 96% were mild, 3% were moderate and 1% were severe (but none of these were judged to be vaccine-related). Pre-vaccination mycobacterial exposure did not affect the adverse event profile. The size of local reaction and frequency of systemic adverse events increased with MVA85A vaccine dose. There were no documented fevers in the low-dose group, whilst 3% of subjects in the combined mid-dose group and 21% in the high-dose group had documented fevers. Peak local reactions were larger after a second poxvirus vaccination, but other local and systemic adverse events were comparable to a single MVA85A vaccination. No severe systemic AEs or serious adverse events in any group were judged to be vaccine-related. Local AEs compared favourably to BCG vaccine-induced local AE and systemic AEs after MVA85A vaccination were comparable to those after the live viral Yellow Fever vaccine in similar populations. There were no correlations found between local reaction size or body temperature and adaptive immune responses (measured by ex vivo interferon gamma Enzyme Linked Immunospot). Conclusions: The candidate TB vaccine, MVA85A has been safely administered to over 100 healthy adults in the UK. Intradermal vaccination with MVA85A induced a transient, superficial reaction local to the injection site and mild short-lived viral symptoms. The local and systemic AE profile of MVA85A vaccination was comparable to published data of other intradermal vaccines and live viral vaccines respectively. Local reaction sizes and body temperature measurements did not correlate with the adaptive cellular immune response to MVA85A. © 2012 Elsevier Ltd.